Electromechanical properties in CaTiO3modified Na0.5Bi0.5TiO3-BaTiO3solid solutions above morphotropic phase boundary - Jurjans, M.; Bikše, Līga; Birks, Eriks; Svirskas, Š.; Antonova, M.; Kundzins, Maris; Sternberg, Andris (American Institute of Physics Inc., 2022)
The structural, electromechanical, and dielectric properties of (1-x)(0.8Na0.5Bi0.5TiO3-0.2BaTiO3)-xCaTiO3 [(1-x) (0.8NBT-0.2BT)-xCT] ceramics are studied as candidates for room temperature actuators with high field-induced strain. The choice of 0.8NBT-0.2BT as a starting composition is motivated by the large tetragonality in this concentration range, even though it is located far away from the morphotropic phase boundary. CaTiO3 was chosen as a third component to decrease the depolarization temperature and achieve a high field-induced strain at room temperature. The measured strains at the field-induced phase transition are remarkably lower than might be expected from the jump in unit cell parameters at the phase transition. This inconsistency could be related to an incomplete field-induced phase transition from the ferroelectric phase to the nonpolar phase. Among all of the manufactured samples, the phase transition is close to room temperature in the composition with x = 0.100, which allows obtaining unipolar strains up to 0.23% at E = 65 kV/cm. Electrostrictive-like strain was observed not only above the depolarization temperature but also in the region of field-induced phase transition. © 2022 Author(s). --//-- Article Jurjans M., Bikse L., Birks E., Svirskas Š., Antonova M., Kundzins M., Sternberg A., "Electromechanical properties in CaTiO3modified Na0.5Bi0.5TiO3-BaTiO3solid solutions above morphotropic phase boundary" (2022) AIP Advances, 12 (3), art. no. 035124, DOI: 10.1063/5.0072329 published under CC BY 3.0 licence.
This work was supported by Mutual funds Taiwan–Latvia–Lithuania cooperation project (Application No. LV-LT-TW/2020/10). The Institute of Solid State Physics, University of Latvia at the Center of Excellence, received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under Grant Agreement No. 739508, project CAMART.2 This project also received funding from the Research Council of Lithuania (LMTLT; Agreement No. S-LLT-20-4). The authors are also indebted to D. Bocharov for technical assistance.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics